Pengaruh FOMO (Fear of missing out) Terhadap Minat Beli Di Common Space Coffee & Bar Batam - Bram Handoko; Wahyudi Ilham; Natal Olotua Sipayung; Dailami . (CV. ITTC INDONESIA, 2025)
This study aims to examine the influence of Fear of FOMO (Fear of missing out) on consumer purchase intention at Café Common Space Batam. FOMO is a psychological phenomenon that manifests as an individual’s urge to follow ongoing trends and avoid the feeling of being left behind. This research applies a quantitative associative-causal approach with a population consisting of all visitors of Common Space Batam over the past six months. The sample size was determined using the Slovin formula with a 10% margin of error, setting the minimum number of respondents at 100, while this study successfully collected 107 valid responses. Data were gathered through a five-point Likert-scale questionnaire and analyzed using simple linear regression. The findings indicate that FOMO has a positive and significant effect on consumers’ purchase intention, with a coefficient of determination (R²) of 0.777 and a significance value of 0.000 (<0.05). These results contribute theoretically to the development of consumer behavior studies and provide practical insights for food and beverage business practitioners in utilizing social media as an effective marketing strategy.